Transformation and resilience processes in mountain oases at the High Atlas (Morocco) – the case of Aït Mrau, Mgoun Valley. - Asencio-Juncal, Jorge; López-Osorio, José Manuel; Rosa-Jiménez, Carlos (Emerald, 2022)
Purpose This study aims to present the uniqueness of the mountain oasis at the High Atlas (Morocco), and is part of a more extensive study about the landscape, the architecture, and the tourist development in the Mgoun Valley. Several natural and anthropogenic factors, such as new environmental conditions and socio-cultural realities, are testing the balance of the system and its adaptive capacity. The study of the values of this territory and its transformation vectors constitute a first step for valuing this ecosystem and being able to establish management and conservation policies. Design/methodology/approach The research is based on the fieldwork carried out over six campaigns, between September 2011 and January 2020, when interviews to the local population and graphic and photographic records of the Aït Mrau oasis were carried out. The work started from the literature review and the study of the origin of the settlement, analyzing the transformation processes both in the cultivated plots and in the built habitat, where the urban evolution of the settlements and the characteristics of the architecture have been analysed. Findings The study has revealed the existence of social, environmental and economic imbalances that affect the status of the oasis, the landscape and the architecture of the study area. The research has characterized the habitat, and has identified those elements that must be preserved to guarantee the permanence of the heritage values in a way that the future development of the region was not conditioned. Originallity/value The research delves into the study of a case that is paradigmatic in the context of the Moroccan High Atlas, since it shows the dynamics of transformation of a region directly affected by the climate change and by the abandonment of the traditional habitats.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/19475
Keywords: Alto Atlas (Marruecos, Cordillera) - Aspectos ambientales; Turismo - Alto Atlas (Marruecos, Cordillera); Oasis; Territory; Environmental fragility; Ecosystem; Cultural identity; Water culture; Vernacular heritage; Earth architecture